Amplitude and phase modulation in microwave ring resonators by doped CVD graphene. (5th June 2018) - Grande, M; Bianco, G V; Capezzuto, P; Petruzzelli, V; Prudenzano, F; Scalora, M; Bruno, G; D'Orazio, A
Abstract: In this paper, we numerically and experimentally demonstrate how to modulate the amplitude and phase of a microwave ring resonator by means of few-layers chemical vapour deposition graphene. In particular, both numerical and experimental results show a modulation of about 10 dB and a 90 degrees-shift (quadrature phase shift) when the graphene sheet-resistance is varied. These findings prove once again that graphene could be efficiently exploited for the dynamically tuning and modulation of microwave devices fostering the realization of (i) innovative beam-steering and beam-forming systems and (ii) graphene-based sensors.